Antiparasitic effect of essential oils obtained from two species of Piper L. native to the Atlantic forest. (March 2021) - Vega Gomez, Maria Celeste; Rolón, Míriam; Coronel, Cathia; Pereira Carneiro, Joara Nályda; Lucas dos Santos, Antonia Thassya; Almeida-Bezerra, José Weverton; Almeida de Menezes, Saulo; Everson da Silva, Luiz; Melo Coutinho, Henrique Douglas; do Amaral, Wanderlei; Ribeiro-Filho, Jaime; Bezerra Morais-Braga, Maria Flaviana
Abstract: Neglected tropical diseases such as leishmaniasis and Chagas disease have difficult management, as their causative agents demonstrate resistance to the currently available drugs. Therefore, the development of novel antiparasitic compounds is urgent. This study investigated the chemical composition, cytotoxicity and antiparasitic activities of the essential oils of Piper diospyrifolium (EOPD) and Piper mikanianum (EOPM). The chemical composition was determined by gas chromatography coupled to mass spectrometry. The anti-parasitic activity was assessed using Leishmania spp. promastigotes and T. cruzi epimastigotes. The cytotoxicity of the essential oils was determined using the murine line of fibroblasts 929 NTCT. The phenylpropanoids (Z)-carpacin and safrole were identified as major compounds in the essential oils of P. diospyrifolium and P. mikanianum, respectively. At highest concentration (1000 μg/mL), none of the of essential oils caused 100% of the lethality in T. cruzi epimastigotes . The DPO presented significant anti-parasitic action against L. braziliensis at concentrations above 31.25 μg/mL (35.34% inhibition), reaching maximum effect (100% inhibition) at 1000 μg/mL. At the same concentration, the EOPM caused 94.25% mortality. The DPO also caused 100% mortality of L. infantum at 1000 μg/mL, demonstrating promising antiparasitic activity against this strain. The essential oils exhibited low cytotoxicity when compared to standard antiparasitic drugs, indicating that are promising sources of new compounds with antiparasitic activity. Highlights: The essential oils of P. diospyrifolium and P. mikanianum have not activity against T. cruzi epimastigotes. Both essential oils showed excellent activity against L. infantum and L. brasiliensis. These EOs had with low cytotoxicity against mammalian cells.